Dynamic Language Learning Tools - Schwartz, Lee; Aikawa, Takako; Pahud, Michel (InSTIL/ICALL2004 Symposium on Computer-Assisted Language Learning, 2004)
In this paper, we present prototypes of individualized language learning tools. We show how Natural Language Processing (NLP) technology developed at Microsoft Research (MSR) facilitates the dynamic creation of language exercises and provides new user experiences in language learning, while raising the bar for educational technology. We demonstrate how our technology, with its rich linguistic resources, enables the dynamic creation of language exercises which are individualized and user-centric. We present some user scenarios to illustrate the flexibility and unlimited potential of our language learning tools. We show that with innovative ideas and vision, our NLP technology can shed new light on the way technology is used in language learning/teaching.